When monetarisation and ranking are not appropriate. A novel stakeholder-based appraisal method. (February 2022) - te Boveldt, Geert; Keseru, Imre; Macharis, Cathy
Abstract: Although there is general consensus on the necessity of evaluation for decision support in major transport projects, there is no method that is universally accepted. Multi-criteria analysis (MCA) is often suggested as the alternative for the dominant but much-criticised (social) cost benefit analysis (CBA), especially in complex multi-stakeholder projects. The paper argues that especially in this type of projects the applicability of conventional MCA techniques is limited because they require the project to be structured as a ranking-choice problem with multiple well-defined mutually exclusive decision alternatives. This often does not suit the planning question in the strategic early project phase, which is characterised by uncertainties relating to design, preferences and impacts. This article proposes a novel evaluation technique, Stakeholder-based Impact Scoring, the primary purpose of which is not to rank alternatives but to identify their positive and negative impacts for multiple stakeholders, in order to support the iterative improvement rather than the mere selection or rejection of alternatives. It is based on two principles: non-compensation, i.e. distinguishing positive and negative impacts; and non-relativity, i.e. the feature that alternatives are scored in comparison to a universal baseline scenario, instead of as relative to one another. The article demonstrates the technique in a project that concerns the reconfiguration of a large elevated urban motorway in Brussels, showing the added value of the method in highlighting key points of discord between stakeholders.